Finding Distinctions between Synonyms - Jelaska, Zrinka (2001)
The active level of lexical knowledge concerning the synonymic words, demonstrated by producing sentences where words and expressions are used appropriately, could be partially achieved through explicit study of vocabulary. Manuals such as dictionaries of one's own or foreign language that list synonimic and related words and explain their specific features are of a great help. The problem is how to find distinguishing features of each pair or group of synonimic and related words where there is no written source to help, when one is faced just with lists of synonimic and related, as is the case in many bilingual dictionaries so far. Native speakers are often vague, even unreliable in defining synonymic differences. The authors propose various types of procedures in collecting the data on similar and related words, which could be very useful for linguistic fieldwork too.